A Typical Skill 4.0 Platform for Process Safety Management - Mokhtarname, Reyhane; Safavi, Ali Akbar; Urbas, Leonhard; Salimi, Fabienne; Taghipour, Hosein (2022 8th International Conference on Control, Instrumentation and Automation (ICCIA), 2022)
In the 20 th century, the engineering curriculum aimed to educate the specialist engineers. Observation skills were enforced after learning the fundamental theory of the scientific and engineering topic in face-to-face classrooms where professors taught the subject matter. Students were engaged in the courses upon the available time and with the professor teaching style. Along the fourth industrial revolution, new engineering education platforms based on some new and desired skills are required to cope with the changes in production and quality assurance requirements. This paper proposes an active collaborative learning platform in which the learners can learn by doing and serious engagement. The developed platform provides the digital twin of process safety engineering and management systems for a real complex polymerization plant. This platform can be used for training of engineers at both academia and industry.